Linguistic Thought in Moschopoulean Schedography - Wahlgren, Staffan (Classica et Mediaevalia, 2025)
This paper contains a discussion of the Περὶ σχεδῶν of Manuel Moschopoulos (ca. 1265-1316), with a special focus on his treatment of the topics of pronunciation and spelling (1), preposition and case (2), and etymology and derivation (3). The purpose is to show how the linguistic thought contained in older grammars, from antiquity and the Byzantine era, is translated into what may be the need of students.